Study on Influences of Linen Fiber Modification Treatment on Dressing Prickle Sensation (Journal of Fiber Bioengineering and Informatics, 2015)
Prickle sensation is a key factor influencing the comfort of dressing. In this paper, the diameter, quantityand fiber bending property of hairiness on the surface of linen fabrics are measured after modificationtreatment of linen fiber. Meanwhile, the prickle sensation of linen clothing is evaluated by dressingexperiments. And the changes of surface hairiness, fiber bending performance and their influences onthe dressing prickle sensation of linen clothing are analyzed before or after the modification treatmentof linen fiber. The results show that the diameter of the surface hairiness becomes thinner and muchmore in quantity after modification treatment, but the bending rigidity decreases. Furthermore, theperception value of prickle sensation of linen clothing after modification treatment decreases whether itis under sweating condition or not.
Keywords: Prickle Sensation; Linen; Dressing; Modification Treatment